Оптимизация краткосрочной валютной политики на базе портфельной теории - Домрачев, В.Н.; Ненахов, Э.И. (Теорія оптимальних рішень, 2007)
There is the question of economic ground of fixing of course of hryvnya against US dollar in the conditions of surplus currency backlogs and tendency to devaluation of dollar in the world currency markets. The macroeconomic aspects of currency policy and dependence of course policy from the structure of export-import are examined in work.